2014
DOI: 10.1007/s12663-014-0663-3
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Antilingula and Its Relation to the Lingula and Mandibular Foramen, the Presence of Mylohyoid Bridging in Dry Mandibles of South Indian Population

Abstract: Background and Objectives The mandibular foramen and the lingula, because of their relation to the inferior alveolar nerve are of clinical significance for the orodental surgeons. Identification of the antilingula is important in mandibular ramus surgery in which the medial surface of the ramus is not visualized. Methods The present study includes adult dry 50 mandibles of unknown age and sex. The measurements were taken using vernier calipers. The points taken for measurements were most prominent point on ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In a study by Apinhasmit et al [ 9 ] using 92 dry mandibles, the antilingula was found in 80.4% of the patients, and it was confirmed that the antilingula was primarily present in the anterior-inferior region of the lingula. In a study by Hosapatna et al [ 12 ] using 50 South Indian dry mandibles, it was confirmed that the mandibular foramen existed in the posterosuperior region of the antilingula, in contrast to the findings of previous studies. In the present study, the lingula was present in posterosuperior region of the antilingula.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In a study by Apinhasmit et al [ 9 ] using 92 dry mandibles, the antilingula was found in 80.4% of the patients, and it was confirmed that the antilingula was primarily present in the anterior-inferior region of the lingula. In a study by Hosapatna et al [ 12 ] using 50 South Indian dry mandibles, it was confirmed that the mandibular foramen existed in the posterosuperior region of the antilingula, in contrast to the findings of previous studies. In the present study, the lingula was present in posterosuperior region of the antilingula.…”
Section: Discussionmentioning
confidence: 83%
“…To prevent this complication, there have been several attempts to develop novel surgical techniques to avoid damage to the IANB during osteotomy of the lateral side of the ramus, such as VRO, inverted L-osteotomy, and C-shaped osteotomy. In order to identify the theoretical basis of these surgical techniques, there have been many studies to determine the anatomical location of the IANB in the lateral side of ramus [ 3 6 , 8 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hosapatna et al [ 18 ] studied 50 dry mandibles and observed that the antilingula was located on the right side of 25 of the mandibles and on the left side of 28 of the mandibles. Hsiao et al [ 19 ] reported the bilateral presence of the antilingula in 67.8% of those studied.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopy has used to visualize the mandibular foramen and related structures and demonstrated that the mylohyoid groove could be doubled, narrowed, or occasionally covered by a bony bridge [29]. The frequency of mylohyoid bridging has been reported as 10.99% (21/191) [30], 10.0% (4/40) [31], and 6.0% (3/50) [32]. Fabian concluded that the formation of the medial wall of the mandibular foramen and/or attachment of the sphenomandibular ligament onto the lingula leads to variations in location of the mylohyoid groove [33].…”
Section: Anatomic Variations Of the Nm And The Mylohyoid Groovementioning
confidence: 99%